Oncogene-Selective Sensitivity to Synchronous Cell Death following Modulation of the Amino Acid Nutrient Cystine - Poursaitidis, Ioannis; Wang, Xiaomeng; Crighton, Thomas; Labuschagne, Christiaan; Mason, David; Cramer, Shira L.; Triplett, Kendra; Roy, Rajat; Pardo, Olivier E.; Seckl, Michael J.; Rowlinson, Scott W.; Stone, Everett; et al. (Cell reports (Cambridge), 2017)
Cancer cells reprogram their metabolism, altering both uptake and utilization of extracellular nutrients. We individually depleted amino acid nutrients from isogenic cells expressing commonly activated oncogenes to identify correspondences between nutrient supply and viability. In HME (human mammary epithelial) cells, deprivation of cystine led to increased cell death in cells expressing an activated epidermal growth factor receptor (EGFR) mutant. Cell death occurred via synchronous ferroptosis, with generation of reactive oxygen species (ROS). Hydrogen peroxide promoted cell death, as both catalase and inhibition of NADPH oxidase 4 (NOX4) blocked ferroptosis. Blockade of EGFR or mitogen-activated protein kinase (MAPK) signaling similarly protected cells from ferroptosis, whereas treatment of xenografts derived from EGFR mutant non-small-cell lung cancer (NSCLC) with a cystine-depleting enzyme inhibited tumor growth in mice. Collectively, our results identify a potentially exploitable sensitization of some EGFR/MAPK-driven tumors to ferroptosis following cystine depletion. [Display omitted] •A nutrient depletion screen revealed a selective role for cystine in promoting viability•Cystine was shown to promote viability by preventing ferroptosis•Sensitivity to depletion of cystine was related to activation of MAPK•Depletion of cystine inhibited tumor growth in a NSCLC xenograft model Poursaitidis et al. show that EGFR and BRAF mutant cells are sensitive to ferroptosis. Sensitivity was related to activation of MAPK signaling and the generation and release of hydrogen peroxide. To show that this sensitivity can be exploited therapeutically, growth of an EGFR mutant NSCLC xenograft was inhibited by a cyst(e)ine-degrading enzyme.